3-Bromopyruvate enhances TRAIL-induced apoptosis in human nasopharyngeal carcinoma cells through CHOP-dependent upregulation of TRAIL-R2. Issue 7 (August 2017) - Can, Zhou; Lele, Song; Zhirui, Zhang; Qiong, Pan; Yuzhong, Chen; Lingling, Liu; Surong, Zhao; Yiming, Sun; Pei, Zhang; Chenchen, Jiang; Liu, Hao
Abstract : Past reports have shown that the sensitivity of cancer cells to TRAIL-induced apoptosis is related to their expression of TRAIL-death receptors on the cell surface. However, the level of TRAIL-death receptors expression on cancer cells is always low. Our previous research showed that nasopharyngeal carcinoma (NPC) cells have a poor sensitivity to low doses of TRAIL. Here, we evaluated combined treatment with the energy inhibitor 3-bromopyruvate (3BP) and TRAIL as a method to produce an increased apoptotic response in NPC cells. The results showed that 3BP and TRAIL together produced higher cytotoxicity and increased TRAIL-R2 expression in NPC cells compared with the effects of either 3BP or TRAIL alone. These findings led us to hypothesize that 3BP may sensitize NPC cells to TRAIL. 3BP is a metabolic blocker that inhibits hexokinase II activity, suppresses ATP production, and induces endoplasmic reticulum (ER) stress. Our results showed that 3BP also activated AMP-activated protein kinase, which we found to play an important role in the induction of ER stress by 3BP. Furthermore, the induction of TRAIL-R2 expression and the sensitization of the NPC cells to TRAIL by 3BP were reduced when we inhibited the expression of CHOP. Taken together, our results showed that a low dose of 3BP sensitized NPC cells to TRAIL-induced apoptosis by the upregulation of CHOP, which was mediated by the activation of AMP-activated protein kinase and ER stress. The results showed that 3BP is a promising candidate agent for enhancing the therapeutic response to TRAIL in NPC.